Engineering of a fluorescent chemogenetic reporter with tunable color for advanced live-cell imaging - Hela Benaissa (Nature Portfolio, 2021)
Fluorescent reporters spanning the visible spectrum are needed for imaging live cells and organisms. Here the authors report a collection of fluorogenic chromophores that cover the visible spectrum from blue to red using a single engineered and optimised protein tag.